PENGARUH PENGGUNAAN TEKNIK PEMODELAN TERHADAP KETERAMPILAN MENULIS NASKAH DRAMA SATU BABAK SISWA KELAS VIII SMP NEGERI 11 PADANG - Ellya Ratna,, Emi Suryani, Yasnur Asri, (Universitas Negeri Padang, 2017)
The aim of this research is to analyze the effect of implementation modeling techniques toward writing a script drama one round skill eight grade students of SMP Negeri 11 Padang. This research is quantitative research. The sampling technique used is purposive sampling, the obtainable based on the sampling technique are VIII.A class as sample of this research. The result of this research is there was a significant effect of the implementation of modeling techniques toward writing a script drama one round skill eight grade students of SMP Negeri 11 Padang by freedom degree (n1 + n2)-2 with significants rate 95% and tobservationÂ is bigger than ttabel that is 7,20>1,70. It means, modeling techniques was effective use in writing a script drama one round r of observation skill eight grade students of SMP Negeri 11 Padang. Observe the benefit and effectiveness of modeling techniques, it proved that modeling techniques can use as reference and developing of inovation toward writing a script drama one round skill.Â Kata kunci: keterampilan menulis, teknik pemodelan, naskah drama satu babak